Adaptation and validation of the Physical Restraint-Theory of Planned Behaviour Questionnaire to the paediatric context - Bosch Alcaraz PhD, Alejandro; Carrionero Alegre RN, Jesús; Belda Hofheinz PhD, Sylvia; Zurigel Pérez PhD, Esperanza; Saz Roy PhD, M. Ángeles; González Rivas RN, Susana; Espildora González RN, María José; Carracedo Muñoz RN, Eva; Lozano Almendral RN, Gema; Morales Cervera RN, David; Mata Ferro RN, María MSc; Serradell Orea RN, Marta; et al. (Wiley, 2025)
Background: Physical restraint is applied in pediatric intensive care units to carry out certain painful procedures and to ensure the maintenance and continuity of life support devices. There is a need to analyse the factors that influence the behaviour or intention to use physical restraint. Aim: To create and test psychometrically a paediatric version of the Physical Restraint-Theory of Planned Behaviour Questionnaire to assess paediatric critical care nurses' intention to use physical restraint. Study Design: A psychometric study. Five medical-surgical Paeditric Intensive care Units from five hospitals in Spain. The study took place in three phases. In phase 1, the questionnaire was adapted. In phase 2, the content validity of each item was determined, and a pilot test was conducted. In phase 3, we administered the questionnaire and determined its psychometric properties. Results: The assessment of the intention to use physical restraint was extended to all critical paediatric patients, two items were eliminated from the initial questionnaire, four new items were included, and the clinical scenarios of the intention subscale were expanded from three to six. Overall content validity index for the full instrument of 0.96 out of 1. The Paediatric Physical Restraint-Theory of Planned Behaviour Questionnaire is made up of four subscales (attitude, subjective norms (SN), perceived behavioural control (PBC), and intention) subdivided into 7 factors and 51 items. The internal consistency for the attitude subscale obtained a Cronbach's Alpha of 0.80 to 0.73, for the SN it was 0.72 to 0.89, for the PBC it was from 0.80 to 0.73 and for the intention subscale it was 0.75. Conclusions: The Paediatric Physical Restraint-Theory of Planned Behaviour Questionnaire is an instrument composed of seven factors and 51 items that validly and reliably assesses the intention of paediatric nurses to apply PR in PICUs. Relevance for Clinical Practice: Having this instrument will help health centres move towards restraint-free care by allowing managers to assess professionals' attitudes, beliefs, and intentions around the use of PR in PICUs.